The Role Of The State And The Transnational In Lifting The Resource Curse - Werner, Karolina (Journal of Sustainable Development Law and Policy, 2025)
In the past, natural resources such as coal and iron ore were catalysts for development and the economic theory focused mainlyon how the exploitation of natural resources could promote trade and development. Since the 1970s, however, we have been increasingly confronted with resource-rich countries lagging behind in economic growth and facing high risks of violent conflict. Using Sierra Leone as a case study, this article briefly explores the resource curse paradox, noting the role of the national government and international actors in maintaining the status quo. It highlights the fragile state of postconflict governments, focusing on the delicate balance between attracting foreign investment and fighting corruption and poverty in environments already susceptible to recurring violence. The article further examines both government and private sector activities that have contributed to the economies of violence through unequal distribution of natural resource rents and revenues. It also argues that to move from resource curse to resource blessing, both the affected states and the international community need to refocus their attention on the effectiveness of returns on natural resource revenues and the critical role of transnational corporations in perpetuating the curse.